ANALYSIS ON THE IMPOSITION OF ONLINE REKLAME TAX ACCORDING TO LAW NUMBER 28 OF 2009 - Rizky Pratama Jawahir; Catur Wido Haruni; Fitria Esfandiari (Universitas Muhammadiyah Tangerang, 2021)
This research about the imposition of online billboard tax as reviewed from article 49 of law number 28 of 2009 concerning regional taxes and regional retribution. The research discusses tax imposition arrangements tax-based advertisements online on the Internet and social media as well as the legal implications of not being regulated as the basis for tax-based advertisements online the internet and social media. Because there are differences in tax treatment between the implementation of conventional advertisements with the based advertisements online. Conventional advertisements are taxed in accordance with the Regional Tax and Retribution Law. However, unlike the case with the advertisement on the internet and social media. This research uses normative juridical research. The approaches that are using are statute approach and conceptual approach. By using this approach can find online advertisements tax imposition arrangements tax based advertisements online on the Internet and social media as well as the legal implications of not being regulated the basis for tax based advertisements online the internet and social media. Based on this research of results, there are several provisions such as the Law on General Provisions and Tax Procedures, Act Income Tax and also the act of Value Added tax. However, conceptually, it is still unable to reach in detail the implementation of the tax based advertisements online. So that a legal vacuum, legal uncertainty in tax imposition and the gap in the value of justice in tax imposition. Based on this, it should be the Government strengthening the Laws and Regulations relating to Taxation. Then, collaborate with other government agencies in the field of communication and information technology. There is a need for a special provision that can accommodate the imposition of this online-based advertisement tax which is carried out through social media and the internet.